2020
DOI: 10.1021/acsinfecdis.0c00606
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of the Nonribosomal Peptide Synthetase BpsA to Enable Recognition by the Human Phosphopantetheinyl Transferase for Counter-Screening Antibiotic Candidates

Abstract: Bacterial type II phosphopantetheinyl transferases (PPTases), required for the activation of many cellular mega-synthases, have been validated as promising drug targets in several pathogens. Activation of the blue-pigment-synthesizing nonribosomal peptide synthetase BpsA by a target PPTase can be used to screen in vitro for new antibiotic candidates from chemical libraries. For a complete screening platform, there is a need to also counter-screen inhibitors for cross-reactivity with the endogenous human Type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…We next sought to benchmark our DMSO-resolubilisation end-point assay against the kinetic assay we had previously described [ 22 ]. For this, we selected two compounds with different inhibition profiles, namely 6-nitroso-1,2-benzopyrone, which has been shown to have activity in vitro against numerous PPTases [ 19 , 22 , 35 ] and in vivo against the fungus Aspergillus fumigatus in a PPTase dependant manner [ 36 ], and the weaker inhibitor sanguinarine chloride, which has been previously reported as an inhibitor of both Sfp from B. subtilis [ 21 ] and M. tuberculosis PptT [ 16 ]. We used identical enzymatic concentrations across both assays to permit a direct comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next sought to benchmark our DMSO-resolubilisation end-point assay against the kinetic assay we had previously described [ 22 ]. For this, we selected two compounds with different inhibition profiles, namely 6-nitroso-1,2-benzopyrone, which has been shown to have activity in vitro against numerous PPTases [ 19 , 22 , 35 ] and in vivo against the fungus Aspergillus fumigatus in a PPTase dependant manner [ 36 ], and the weaker inhibitor sanguinarine chloride, which has been previously reported as an inhibitor of both Sfp from B. subtilis [ 21 ] and M. tuberculosis PptT [ 16 ]. We used identical enzymatic concentrations across both assays to permit a direct comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Our assay therefore meets a need for a simple high-throughput assay that can be applied to directly screen for inhibitors of PptT or other Type II PPTases, or to guide the development of next-generation drug leads based on promising scaffolds such as ML-267 and 8918. Recently, we have also shown that the PCP-domain of BpsA can be rapidly evolved using error-prone mutagenesis to be recognised by other Type II PPTases that initially cannot activate BpsA [ 35 ]. This provides a platform to enable the rapid integration of multiple PPTases for inhibitory activity, or to counter-screen the endogenous human PPTase to eliminate drug candidates likely to have undesirable off-target effects.…”
Section: Discussionmentioning
confidence: 99%